Dupilumab in children and adolescents with atopic dermatitis, a 52-week real-life experience: first report in Colombia - Daniela Meléndrez Vásquez; María Fernanda Ordoñez-Rubiano; Daniela Marín-Acevedo (Revista de la Asociación Colombiana de Dermatología y Cirugía Dermatológica, 2024)
Atopic dermatitis (AD) is a chronic inflammatory disease characterized by relapsing eczema and pruritus. Recently, dupilumab has shown to be safe and improve symptoms of moderate to severe AD in adolescents up to 52 weeks, however, very few Latin American patients were included, so comprehensive real-world data is needed. To our knowledge, there are no real-world studies published in this ethnicity regarding long-term treatment with Dupilumab for AD in adolescents.